RURAL ENTREPRENEURSHIP STRATEGIC PLANNING A COGNITION PERSPECTIVE - Laksono, Ferrynela Purbo (Manajemen dan Bisnis, 2023)
The purpose of this paper is to explore the cognition aspects of strategic planning in rural entrepreneurship. The research is a case study in Patuk sub-district, Gunung Kidul district, Special Region of Yogyakarta. Patuk Sub-district has great potential. Rural entrepreneurs can develop it. Cognition aspects are determinants for rural entrepreneurs. This research is qualitative research using a case study. The method in this research uses in-depth interviews and FDG. The result of the research is that the cognition aspect is one of the determinants of success in determining the strategic planing. With sufficient knowledge, rural entrepreneurs can develop the right strategic planning, so they can compete and survive. Unfortunately, their knowledge is limited. The cognitive aspect comes from the rural internal environment and the rural external environment The rural internal environment itself consists of rural communities where entrepreneurs are located.. The value adopted by rural communities has an impact on rural entrepreneurship. The external environment is a support system from outside the community. The rural entrepreneurs need a support system. For this reason, rural entrepreneurs need external encouragement. The external environment comes from the government and universities. The government provides support in the form of policies and programs that support rural entrepreneurs. Universities provide knowledge for business development